Family Dialogue of Kindergarten’s Parents and its Relation to Children’s Fears (Journal Of Educational and Psychological Researches, 2022)
The research aims at Identifying family dialogue of kindergarten’s parents. 2)  Exploring the fears that kindergarteners suffer from. 3) Identifying family dialogue of kindergarteners’ parents and the fears of their children. To achieve the aim of the research, the researcher designed two scales: one for the family dialogue of kindergarteners’ parents, and the other for the fears of the kindergarten’s child. To identify the relationship between these two elements, the scale subjected to the consultation of a group of specialized expertise in educational and psychological sciences to certify the propriety of the items. The reliability of the scale of the family dialogue recorded (0.85). As for the scale of children’s fears, it has founded to be (0.88). The sample of the research consisted of (90) families. The research came up with the following results: There is a family dialogue of kindergarten’s parents. There are no fears that kindergarteners suffer from. There is an Inverse relationship between family dialogue of kindergarteners’ parents and the children’s fears.